WORK ALLOCATION IN COMPLEX PRODUCTION PROCESSES: A METHODOLOGY FOR DECISION SUPPORT - de Mello, Adriana Marotti (2011)
This article presents the development of a Methodology of Decision Support for Work Allocation in complex production processes. It is known that this decision is frequently taken empirically and that the methodologies available to support it are few and restricted in terms of its conceptual basis. The study of Times and Motion is one of these methodologies, but its applicability is restricted in cases of more complex production processes. The method presented here was developed as a result of a project coordinated by the authors, on demand by a large Brazilian petrochemical company. An Action Research based approach was used to develop the method, based on the generation of alternative scenarios offering different possibilities for work allocation. This paper aims to contribute to the literature on the theme, starting from a premise that it is necessary to develop a method that organizes information and, as much as possible, makes explicit the premises and the consequences that decisions on work allocation might cause.